Heat-affected coarsening of β grain in titanium alloy during laser directed energy deposition. (December 2021) - Xue, Aitang; Lin, Xin; Wang, Lilin; Lu, Xufei; Ding, Hanlin; Huang, Weidong
Abstract: The heat-affected coarsening of β-grains in titanium alloy produced by additive manufacturing (AM), which would be important for the achievement of fine β-grain like forging, was completely neglected in the past. Here, we reported that the significant coarsening of equiaxed β-grain of Ti6Al4V happened under the instantaneous high-temperature (above β-transus) thermal cycling during laser directed energy deposition process. Especially, the coarsening becomes more striking in the cases of smaller initial β-grain, larger energy density and higher preheating-temperature. Meanwhile, a modified model used to predict the size of the coarsened β-grain of AM titanium alloy was proposed. These findings provide a more comprehensive understanding of the β-grains of AM titanium alloy and a significant guidance for the composition design of AM titanium alloy with fine equiaxed β-grains. Graphical abstract: Image, graphical abstract